Assessment of different Lippia sidoides genotypes regarding their acaricidal activity against Rhipicephalus (Boophilus) microplus - Alexandra Martins dos Santos Soares (Revista Brasileira de Parasitologia Veterinária, 2016)
The aim of this study was to select different genotypes of Lippia sidoides with the highest activity against larvae and engorged females of the tick Rhipicephalus (Boophilus) microplus. The germplasms studied were LSID006, LSID102, LSID103 and LSID104. The LSID104 genotype, that presented carvacrol as a major constituent, was the germplasm with the worst larvicide effect (LC50 2.99 mg/mL). The LSID006 genotype was the least effective against engorged females (LC50 12.46 mg/mL), and it was chemically similar to the LSID102 genotype, which presented the highest acaricide activity (LC50 2.81 mg/mL). We conclude that chemical similarity of the germplasms was not correlated with acaricide activity against R. (B.) microplus. The essential oil of L. sidoides is a potent natural agent. However, the findings of this work provide a better understanding for product development based on this natural product, which must consider synergic effects or the action of minor compounds.